Thermally Stable All‐Perovskite Tandem Solar Cells Fully Using Metal Oxide Charge Transport Layers and Tunnel Junction. Issue 12 (27th October 2021) - Gao, Han; Lu, Qianwen; Xiao, Ke; Han, Qiaolei; Lin, Renxing; Liu, Zhou; Li, Hongjiang; Li, Ludong; Luo, Xin; Gao, Yuan; Wang, Yurui; Wen, Jin; et al.
Abstract : All‐perovskite tandem solar cells offer a promising avenue to go beyond the efficiency limit of single‐junction devices. Their efficiencies have been increasing rapidly in the past few years; however, their commercial viability is hindered by the instability under thermal stressing. Herein, comprehensive device design strategies are proposed to achieve thermally stable all‐perovskite tandem solar cells while retaining the advantages of solution processing. Metal oxides, i.e., NiO x and SnO2, are used for the hole and electron transport layers in both wide bandgap and narrow subcells. The metal‐based recombination layer is replaced with a stable and conductive indium tin oxide nanocrystals film to fabricate an all metal‐oxide‐based tunnel junction. Based on those design strategies, the encapsulated all‐perovskite tandem solar cells retained 85% of their initial efficiency after stressing at 85 °C for 2500 h and maintained >80% of their initial performance after 900 h operation at the maximum power point and operating temperature of ≈65 °C. Achieving such thermal stability represents a crucial step toward commercial viability of all‐perovskite tandem solar cells. Abstract : The design strategy of thermally stable all‐perovskite tandem solar cells is presented, where metal oxides are used for the charge transport layers and tunnel junction. The tandem devices retained 85% of their initial efficiency after thermal stressing at 85 °C for 2500 h. Achieving such remarkable thermal stability represents a crucial step toward commercial viability of all‐perovskite tandem solar cells.